1991
DOI: 10.1111/j.1528-1157.1991.tb04676.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and 31P Spectroscopy of an Interictal Cortical Spike Focus in the Rat

Abstract: Magnetic resonance imaging (MRI) has proven to be an effective noninvasive technique for identifying lesions in patients with temporal lobe epilepsy. It has also been suggested that MRI may be sensitive to transient functional or metabolic changes in brain tissue. Increased brain electrical activity as monitored by electroencephalography causes changes in cerebral metabolism that may be responsible for focal or regional alterations in signal in the MRI of some patients. To test this hypotheses, experimental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…One can assume also that the degree of ictal activity in EEG monitoring should correlate to neuronal dysfunction in 1 H‐MRS, as do interictal EEG patterns. Possible reasons that ictal activity in EEG is not correlated to metabolite alterations in 1 H‐MRS could be that duration of ictal activities often is shorter compared with interictal activity in 24 h. Mechanisms of interictal activity are probably less severe than ictal activity, comprising lower‐energy turnover (Karlik et al, 1991) and therefore less prostrating to neuronal cells, resulting in longer periods of interictal EEG activity.…”
Section: Discussionmentioning
confidence: 99%
“…One can assume also that the degree of ictal activity in EEG monitoring should correlate to neuronal dysfunction in 1 H‐MRS, as do interictal EEG patterns. Possible reasons that ictal activity in EEG is not correlated to metabolite alterations in 1 H‐MRS could be that duration of ictal activities often is shorter compared with interictal activity in 24 h. Mechanisms of interictal activity are probably less severe than ictal activity, comprising lower‐energy turnover (Karlik et al, 1991) and therefore less prostrating to neuronal cells, resulting in longer periods of interictal EEG activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies demonstrated decreased phosphocreatine levels without changes in the levels of ATP and pioneered the idea that NMR techniques can be used for in vivo detection of seizure consequences. The first MRI studies in epilepsy models were conducted in the early 1990s (Karlik et al, 1991; King et al, 1991). Status epilepticus was induced by chemical convulsants such as kainate or pilocarpine, and animals were followed with MRI for a few days.…”
Section: Mri Studies In Animal Models Of Acquired Epilepsy—focus On Smentioning
confidence: 99%
“…31 P MRS may be used in combination with other MRS techniques such as 1 H MRS for the identification of the ictal event itself as an energy exhaustive process. However, it is unlikely that any significant (measurable) change in the pool of high‐energy metabolites occurs during interictal spiking (without an ictal event) that is detectable presently on MRS or MRI (Karlik et al, 1991).…”
Section: P Mrs‐early Studiesmentioning
confidence: 99%